2023
DOI: 10.1038/s41419-023-05597-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18-primed human umbilical cord-mesenchymal stem cells achieve superior therapeutic efficacy for severe viral pneumonia via enhancing T-cell immunosuppression

Abstract: Coronavirus disease 2019 (COVID-19) treatments are still urgently needed for critically and severely ill patients. Human umbilical cord-mesenchymal stem cells (hUC-MSCs) infusion has therapeutic benefits in COVID-19 patients; however, uncertain therapeutic efficacy has been reported in severe patients. In this study, we selected an appropriate cytokine, IL-18, based on the special cytokine expression profile in severe pneumonia of mice induced by H1N1virus to prime hUC-MSCs in vitro and improve the therapeutic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…hUC-MSCs were isolated from UC Wharton’s jelly and cultured according to previously described methods [ 19 ]. These primary cells can be MSCs, including those that undergo tri-lineage differentiation into adipogenic, chondrogenic, and osteogenic cells (Additional file 1: Fig S1 A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hUC-MSCs were isolated from UC Wharton’s jelly and cultured according to previously described methods [ 19 ]. These primary cells can be MSCs, including those that undergo tri-lineage differentiation into adipogenic, chondrogenic, and osteogenic cells (Additional file 1: Fig S1 A ).…”
Section: Resultsmentioning
confidence: 99%
“…It is crucial to study the distinct factors responsible for MSC priming to aid in the treatment of different diseases. Various inflammatory cytokines have been reported to prime MSCs, and their function and therapeutic efficacy have been investigated across different diseases [ 13 19 ]. However, our understanding of the disease microenvironment and its impact on MSC activation requires further development.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs inhibited Th17 and induced Treg differentiation, which led to the attenuation of lung injury caused by the virus ( 65 ). On the other hand, when MSCs were injected in mice with viral pneumonia, attenuated proliferation of both CD3 + , CD4 + and CD4 + , CD8 + T cells was observed, resulting in the significant suppression of pro-inflammation factor level and the protection of mice alveolar epithelial cells from inflammatory injury similar to severe COVID-19 ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, MnSOD-MSCs differentiated into epithelial-like cells in vivo [ 104 ], indicating the excellent capability of MnSOD-MSCs. Also, Liao et al (2023) have found that administration of IL18-hUC-MSCs could drastically decrease viral load, fibrosis, and cell apoptosis in acute lung injuries [ 105 ]. Notably, T cell exudation and pro-inflammatory cytokine release in bronchoalveolar lavage fluid (BALF) were significantly inhibited by IL18-hUCMSC therapy [ 105 ].…”
Section: Pre-conditioned Mscs In Lung Failurementioning
confidence: 99%